Studies on the high-temperature ferroelectric transition of multiferroic hexagonal manganite RMnO3. (15th February 2018) - Sim, Hasung; Jeong, Jaehong; Kim, Haeri; Cheong, S-W; Park, Je-Geun
Abstract: Hexagonal manganites are multiferroic materials with two highly-dissimilar phase transitions: a ferroelectric transition (from P63 /mmc to P63 cm) at a temperature higher than 1000 K and an antiferromagnetic transition at T N   =  65–130 K. Despite its critical relevance to the intriguing ferroelectric domain physics, the details of the ferroelectric transition are not well known to date primarily because of the ultra-high transition temperature. Using high-temperature x-ray diffraction experiments, we show that the ferroelectric transition is a single transition of abrupt order and R–Op displacement is the primary order parameter. This structural transition is then simultaneously accompanied by MnO5 tilting and the subsequent development of electric polarization.